Screening and evaluation of bacterial endophytes of cowpea [Vigna unguiculata (L.) Walp.] for plant growth promotion and biocontrol potential - Siva, M.; Sreeja, S.J.; Thara, Susha S.; Heera, G.; Anith, K.N. (Plant Science Today, 2024)
Cowpea [Vigna unguiculata (L.) Walp], is a popular leguminous vegetable crop grown in the wetland fallows of Kerala, India. Web blight caused by Rhizoctonia solani has turned out to be a problem in cowpeas, leading to substantial yield loss. We isolated 22 endophytic bacteria from fodder cowpea var. Aiswarya and 16 from bush cowpea var. Bhagyalakshmi, and evaluated their plant growth promotion ability and potential for web blight pathogen suppression. Initially, the isolates were screened in vitro for their plant growth promotional traits and antagonism against R. solani. The potential isolates were identified as Bacillus subtilis, B. amyloliquefaciens and B. velezensis through 16S rDNA cataloguing. Plant growth-promoting traits like the production of IAA (Indole acetic acid), ammonia, phosphorus, and siderophore by the promising isolates were also investigated. B. amyloliquefaciens CBSE5 recorded the highest IAA (3.54 microgram/mL) and siderophore production. B. velezensis CBRE5 showed the highest ammonia (177.29 micro moles/mL) production and phosphate solubilization. In the in vivo assay, seed biopriming along with foliar application on 20 and 40 days after sowing, of a consortium of B. amyloliquefaciens CBSE5 and B. velezensis CBRE5 recorded maximum values for all growth parameters viz. shoot length, root length, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, pod yield and number of pods per plant. The present study reports for the first time the use of endophytic Bacillus spp. isolated from cowpeas as plant growth-promoting bacteria, with biocontrol potential against the web blight pathogen R. solani.